Response to "On the Empirical Validity of 'Gendered Reactions to Terrorist Attacks Can Cause Slumps not Bumps'" - Mirya R. Holman; Jennifer L. Merolla; Elizabeth J. Zechmeister (Institute for Replication (I4R), 2023)
Jetter and Stockley (2023) successfully replicate nearly all 140 analyses we report in the original paper and appendix. In the process, they identified two errors. We appreciate this effort and made corrections to the data and code. Revising the analyses to correct these errors results in small changes to the output but does not change the significance, direction, or substantive effects of the central variables in the paper and does not alter our conclusions. The authors of the replication paper then extend their efforts beyond replication and, based on this work, conclude our work "does not provide sufficient support" for a gendered revision to the conventional rally 'round the flag framework. We respectfully disagree with their conclusion because it ignores theory, disregards key components of the critical test case, ignores evidence provided in the article and supplementary materials, revises the empirical approach, and commits to strict p-value cut-offs that risk Type II errors.
Additional information: This paper responds to: Jetter, M., and K. Stockley. 2023. On the Empirical Validity of "Gendered Reactions to Terrorist Attacks Can Cause Slumps not Bumps" (Holman et al., 2022). I4R Discussion Paper Series, No. 41. https://hdl.handle.net/10419/272842
Keywords: 330